2021
DOI: 10.3390/biomedicines9060668
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in Early Response to Brolucizumab on Pigment Epithelium Detachment Associated with Exudative Age-Related Macular Degeneration

Abstract: Background: The purpose of this study was to describe early changes in the morphology of pigment epithelium detachments (PED) after an intravitreal injection of Brolucizumab into eyes with macular neovascularization secondary to exudative age-related macular degeneration (e-AMD). Method: We included twelve eyes of 12 patients with PED secondary to e-AMD which were not responding to prior anti-VEGF treatments. An ophthalmic examination and an assessment of PED-horizontal maximal diameter (PED-HMD), PED-maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 49 publications
6
21
0
Order By: Relevance
“…From the 45 real-world studies (50 reports) for inclusion, 26 studies (31 reports) described at least 10 brolucizumab-treated eyes, and are thus included in the main descriptive summary (Tables 1-3; Tables S1-S3) (Abdin et al, 2021;Aziz et al, 2021;Baumal et al, 2020;Bilgic, Kodjikian, March de Ribot, et al, 2021;Bilgic, Kodjikian, Srivastava, et al, 2021;Book et al, 2022;Bulirsch et al, 2022;Chakraborty et al, 2021;Cristian et al, 2021;Enríquez et al, 2021;Fossataro et al, 2021;Fukuda et al, 2021;Haensli et al, 2021aHaensli et al, , 2021bHamou et al, 2021;Hussain, 2021;Kilani et al, 2021;Maruko et al, 2021;Matsumoto et al, 2021;Montesel et al, 2021;Rave et al, 2021;Reyes-Capo et al, 2021;Rispoli et al, 2021;Sharma, Kumar, et al, 2021;Sharma, Rave, et al, 2021;Sudhalkar et al, 2021;Walter & Saba, 2021aWitkin et al, 2020Witkin et al, , 2021. A further 19 studies (19 reports) describing fewer than 10 brolucizumab-treated eyes are included in Table S4.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the 45 real-world studies (50 reports) for inclusion, 26 studies (31 reports) described at least 10 brolucizumab-treated eyes, and are thus included in the main descriptive summary (Tables 1-3; Tables S1-S3) (Abdin et al, 2021;Aziz et al, 2021;Baumal et al, 2020;Bilgic, Kodjikian, March de Ribot, et al, 2021;Bilgic, Kodjikian, Srivastava, et al, 2021;Book et al, 2022;Bulirsch et al, 2022;Chakraborty et al, 2021;Cristian et al, 2021;Enríquez et al, 2021;Fossataro et al, 2021;Fukuda et al, 2021;Haensli et al, 2021aHaensli et al, , 2021bHamou et al, 2021;Hussain, 2021;Kilani et al, 2021;Maruko et al, 2021;Matsumoto et al, 2021;Montesel et al, 2021;Rave et al, 2021;Reyes-Capo et al, 2021;Rispoli et al, 2021;Sharma, Kumar, et al, 2021;Sharma, Rave, et al, 2021;Sudhalkar et al, 2021;Walter & Saba, 2021aWitkin et al, 2020Witkin et al, , 2021. A further 19 studies (19 reports) describing fewer than 10 brolucizumab-treated eyes are included in Table S4.…”
Section: Search Resultsmentioning
confidence: 99%
“…Information was limited as to how events were defined and how patients were monitored during follow-up. Six studies reported no adverse events occurring during follow-up (Bilgic, Kodjikian, Srivastava, et al, 2021;Fossataro et al, 2021;Hussain, 2021;Reyes-Capo et al, 2021;Rispoli et al, 2021;Sharma, Kumar, et al, 2021). For three studies, ocular adverse events were an inclusion criterion (Baumal et al, 2020;Witkin et al, 2020Witkin et al, , 2021.…”
Section: Safety Outcomesmentioning
confidence: 99%
“…The response at 1 month after brolucizumab treatment is important to predict the prognosis. A previous study of exudative AMD reported that the PED height was significantly reduced within 1 month after the first brolucizumab injection [27]. It is speculated that one month could be enough to see the responsiveness of brolucizumab.…”
Section: Discussionmentioning
confidence: 95%
“…Brolucizumab, an anti-vascular endothelial growth factor (anti-VEGF) for intravitreal injections (IVI), is the newest drug of its kind to be commercially available in the United States. [1][2][3] This drug, a humanized single-cell chain antibody fragment, constrains VEGF-A attachment to VEGFR1 and VEGFR2, two VEGF receptors. After three monthly loading IVI of both brolucizumab 6mg/0.05mL dosed at 8 or 12 weeks and aflibercept 2mg/0.05mL dosed at 8 weeks, two separate Phase III clinical trials [HAWK (NCT02307682) and HARRIER (NCT02434328)] showed that brolucizumab was non-inferior to the comparative agent in terms of visual acuity for treatment-naïve neovascular age-related macular degeneration (AMD).…”
Section: Introductionmentioning
confidence: 99%